FORMATION OF THE PROFESSIONAL COMPETENCE OF STUDENTS THROUGH THE INTERDISCIPLINARY INTEGRATION OF PHYSICS INTO THE SCIENCES OF ARCHITECTURE AND CONSTRUCTION (Conferencea, 2023)
The article presents the stages of formation of professional competence of students through interdisciplinary integration of architecture and construction sciences in the process of training future builder-engineers from physics in technical higher education institutions.